Devolution and the New Zealand Resource Management Act - Suzi Kerr; Megan Claridge; Dominic Milicich (New Zealand Government, The Treasury, 1998)
Many past and potential New Zealand reforms involve significant devolution, i.e. the transfer of authority to make decisions on behalf of society from a higher to a lower level of government. In particular the Resource Management Act (RMA), the health and education reforms, and decisions about the institutions for addressing Maori issues have led to significant devolution of authority. Employment policy and social welfare are areas where devolution is an important policy option. The role and function of local government also is inherently an issue of the appropriate level of devolution. Many of these reforms have now been in place for a number of years, so it is appropriate to review our experience of devolution, identify the successes, and attempt to address the problems that have arisen. Two papers address issues of when and how we should devolve authority from central to local government. This paper looks at devolution both from a general theoretical standpoint and from the perspective of the New Zealand Resource Management Act 1991 (RMA), with residential land use as an illustration. Although the RMA is discussed throughout both papers, the framework developed applies to any area of policy for which devolution decisions are being considered. The second paper, Treasury Working Paper 98/7a, applies the framework to the optimal pattern of devolution for policies relating to kiwi protection.
Keywords: 330